Potential for Homestay Development in Genggelang Tourism Village, North Lombok Regency - Fahmi, Saiful; Karomi, M. Ihdal (Media Wisata, 2025)
The development of tourist villages is one of the strategies to improve the economy of rural communities. Genggelang Tourism Village in North Lombok Regency has great potential in the tourism sector, with main attractions such as Senara Chocolate Village, Kerta Gangga Waterfall, and local culture that is still preserved. However, the limited number of homestays is an obstacle in utilizing the existing tourism potential. This study aims to identify the causes of the lack of homestay development and explore the potential for its development. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and literature studies. The results of the study indicate that the main obstacles in the development of homestays are minimal community involvement, limited capital, and lack of use of marketing technology. On the other hand, the opportunity for homestay development is quite large with the increase in tourist visits to the Gili Trawangan area, which can make Genggelang Village a buffer area. With synergy between the government, the community, and the use of information technology, the development of homestays in Genggelang Tourism Village has the potential to improve the local economy and strengthen the village's tourism appeal.